(untitled) (Global Journal of Human-Social Science, 2023)
Learner-centred curriculum reforms in developing countries have a long classroom history of nonimplementation The need is to better understand teachers perspectives on such reforms A Typology of Teacher Reactions to Curriculum Reforms provides a nuanced framework to interpret teachers knowledge attitudes and behaviour Divided into three domains and seven categories the typology encompasses the Cognitive Domain ranging from Lack of Awareness to Recognition to Understanding the Affective Domain Espoused Belief and Actual Belief and the Behavioral Domain Surface Practice and Deep Practice The evidence from wide-ranging school effectiveness and classroom improvement literature reviews that illustrate the Typology is that typically interview and questionnaire studies find teachers in primary and secondary schools are aware of learner-centred curriculum policies mandated at higher levels can articulate knowledge about them and express positive attitudes However triangulation with classroom observation commonly shows traditional pedagogy continues Any adoption is of surface features consistent with teacher-centred knowledge transmission rather than student-centred knowledge construction While espoused support can be professionally expedient for teachers non-adoption as theories-in-use can be a reasoned response to curricula that offer no relative advantage are complex incompatible with existing methods and offer no observable outcomes for clients Rather than introducing culturally-inappropriate curriculum reforms a more constructive approach to improving teaching effectiveness is to identify and reverse engineer successful classroom methods that are consistent with teachers understandings of pedagogy and epistemology